Fit for purpose? A review of guides for gender-equitable value chain development - Stoian, D.; Donovan, J.; Elias, Marlène; Blare, T. (Informa UK Limited, 2018)
This article presents a review of seven guides for gender-equitable value chain development (VCD). The guides advocate persuasively the integration of gender into VCD programming and raise important issues for designing more inclusive interventions. However, gaps persist in their coverage of gender-based constraints in collective enterprises, the influence of norms on gender relations, and processes to transform inequitable relations through VCD. Guidance for field implementation and links to complementary value chain tools are also limited. The article identifies opportunities for conceptual and methodological innovation to address the varying roles, needs, and aspirations of women and men in VCD.